2019
DOI: 10.1186/s12903-019-0776-7
|View full text |Cite
|
Sign up to set email alerts
|

Big toenail and hair samples as biomarkers for fluoride exposure – a pilot study

Abstract: Background Biomarkers can aid in detecting and preventing clinical disease through the recognition of change in biological samples. The objective of this case-control study was to further the knowledge on the use of big toenail and hair samples as biomarkers for fluoride exposure. Methods A total of 48 participants from an endemic (IC) and a non-endemic (SC) fluorosis region were included. Big toenail and hair samples were collected from each participant and the fluorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Nails are a noninvasive, readily available biomarker of chronic, subchronic, and acute F exposure. e F concentration found in the toenails confirms its value in measuring a community's chronic F [23,25]. e exposure time reflects the increase in the DF incidence in the birth cohorts and coincides with the F concentration found in the study population's toenails.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Nails are a noninvasive, readily available biomarker of chronic, subchronic, and acute F exposure. e F concentration found in the toenails confirms its value in measuring a community's chronic F [23,25]. e exposure time reflects the increase in the DF incidence in the birth cohorts and coincides with the F concentration found in the study population's toenails.…”
Section: Discussionsupporting
confidence: 77%
“…The F concentration found in the studied cases' toenails coincides with that found in similar studies, i.e., toenail samples, age group, and the number of subjects, conducted in other geographic areas [ 20 ]. Elekdag-Turk et al [ 25 ] found a mean F concentration of 2.34 ± 0.26 mg/kg in endemic regions and a mean of 0.98 ± 0.08 mg/kg in nonendemic regions. Buzalaf et al [ 20 ] and Amaral et al [ 28 ] reported F concentrations of 1.49–2.80 mg/kg and 2.15 (0.39)–2.64 (0.41) μ g F/g, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nails and hair can be highlighted for their capability of reflecting the short-term and long-term exposure to fluorides (from months to years), non-invasive access, and long storage periods without degradation or loss of properties, and because both are supplied by blood during the growth stage, these present the average concentration of plasma fluoride levels from chronic intake [ 23 , 25 , 26 , 27 ]. Furthermore, both nails and hair as keratinized matrices share histological features that make them able to attach different types of elements, which is useful for the toxicological evaluation in several research areas [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In both biomarkers, higher F − levels were found in the endemic fluorosis area, showing significant differences ( p < 0.001 for nails; p = 0.004 for hair). Although it was established that nails and hair were adequate biomarkers for monitoring the exposure to fluorides, toenails had more sensitivity for this purpose [ 25 ].…”
Section: Discussionmentioning
confidence: 99%